2022
DOI: 10.12932/ap-080719-0596
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and predictors of nevirapine and efavirenz-associated rash among Indonesian HIV patients

Abstract: Background: Many drugs used for the treatment of HIV disease can cause drug hypersensitivity reactions. Since 2002, World Health Organization (WHO) has recommended the use of nevirapine and efavirenz as part of first line antiretroviral therapies for several years. Both of the drugs had equivalent clinical efficacy but differences in toxicity profile.Objectives: We aimed to determine the incidence and predictors of nevirapine and efavirenz-associated rash among Indonesian HIV-infected patients.Methods: A retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Several studies have reported the power of these drugs to reduce cell proliferation and compromise cell viability. The relationship between some NNRTI drugs and the proinflammatory state appears to be critical to understand the pathogenesis of various side effects [ 87 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the power of these drugs to reduce cell proliferation and compromise cell viability. The relationship between some NNRTI drugs and the proinflammatory state appears to be critical to understand the pathogenesis of various side effects [ 87 90 ].…”
Section: Discussionmentioning
confidence: 99%